Pelatihan empati sebagai upaya mengurangi perilaku perundungan pada siswa SMP - Lika, Lika (Persona:Jurnal Psikologi Indonesia, 2019)
AbstractBullying tends to intensify during middle school years, especially amongst students who grew up in harsh environments and were exposed to negative behaviors in their formative years. This research is aimed at assessing the effectiveness of school-based empathy training in preventing bullying behaviors in middle school students. A sample of 25 students was selected using a purposing sampling technique. The two days training was split into six sections i.e. introduction The same group of students was given Pre and Post empathy training evaluation. The two days training consisted of six sections starting from the introduction of the program, baseline assessment, intervention, post-test, playing of video and a closing discussion. Evaluation of the training effectiveness was held a month after the training. The statistical study of pretest and posttest Empathy Training, pretest, and posttest Bullying questionnaires, using Wilcoxon Signed Ranks. The finding indicated that Empathy training resulted in a change of insight and improvement in bullying tendencies.Keywords: Behavior; Empathy training; Bullying  AbstrakFenomena perundungan di lingkungan sekolah, umumnya dilatarbelakangi oleh paparan perilaku agresi (verbal dan Fisik) yang sering dialami sebelumnya oleh pelaku. Penelitian ini bertujuan untuk mengetahui efektivitas pelatihan empati dalam mengurangi perilaku perundungan pada remaja di lingkungan sekolah. Subjek penelitian terdiri dari 25 orang siswa/i yang diperoleh berdasarkan teknik purposive sampling. Perlakuan diberikan selama 2 hari, terdiri dari 6 sesi, yaitu sesi pembukaan, perkenalan, menjelaskan tahapan pelatihan, pengukuran awal, pemberian materi, pretest dan posttest,  pemutaran video dan diskusi. Evaluasi terhadap perubahan perilaku dilakukan sebulan setelah pelatihan diberikan. Uji statistik Pretest dan Posttest Materi Pelatihan Empati serta Pretest dan Posttest skala perundungan dengan menggunakan Tes Wilcoxon Signed Ranks. Hasil menunjukkan terjadinya peningkatan pemahaman peserta mengenai perilaku perundungan serta penurunan kecenderungan memunculkan perilaku perundungan setelah mengikuti pelatihan empati. Kata Kunci: Perundungan, Perilaku, Pelatihan Meningkatkan Empati.